Tingkat Stres dan Perilaku Manajemen Stres Keluarga Orang Dengan Gangguan Jiwa (ODGJ) - Nasriati, Ririn (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Diagnosis of mental disorders and the duration of treatment can lead to tension and despair so thatpsychological stress arises from the families of people with the mental disorders. Psychological stressfamilies of people with mental disorders should be in the management properly so no impact on thetreatment of family members who have mental disorders.The research objective was to analyze the stresslevel relationships with family stress management behaviors of people with mental disorders. The studydesign was a correlation with croossectional approach. The population was the entire family of people withmental disorders were 40 taken with the total sampling and analyzed using Chi Square. Results showedfamilies of people with mental disorders do not stress as much as 29 respondents (72.5%) and positiveattitude as much as 22 respondents (55%). There was a relationship with the stress level of family stressmanagement behaviors of people with mental disorders with p value <0.05.In conclusion the level of stressrelated with family stress management behaviors of people with mental disorders. Stress managementeducation and socialization needs to be done so that the psychological burden of the family can beminimized.